Atomic-scale investigation of hydrogen distribution in a TiMo alloy. (15th March 2019) - Yan, Fengkai; Mouton, Isabelle; Stephenson, Leigh T.; Breen, Andrew J.; Chang, Yanhong; Ponge, Dirk; Raabe, Dierk; Gault, Baptiste
Abstract: Ingress of hydrogen is often linked to catastrophic failure of Ti-alloys. Here, we quantify the hydrogen distribution in fully β and α + β TiMo alloys by using atom probe tomography. Hydrogen does not segregate at grain boundaries in the fully β sample but segregates at some α/β phase boundaries with a composition exceeding 20 at.% in the α + β sample. No stable hydrides were observed in either sample. The hydrogen concentration in β phases linearly decreases from 13 at. % to 4 at. % with increasing Mo-content, which is ascribed to the suppression of hydrogen uptake by Mo addition. Graphical abstract: Unlabelled Image